Low uptake of hypertension care after community hypertension screening events in Lagos, Nigeria - Heleen Elise Nelissen; Tochi Joy Okwor; Oluyemisi Khalidson; Akin Osibogun; Anja Helena Van't Hoog (Taylor & Francis Group, 2018)
Background: In Lagos, Nigeria, approximately 33% of the population suffers from hypertension, yet antihypertensive treatment coverage is low. To improve access to care, a decentralized pharmacy-based hypertension care model was piloted. This study reports on the recruitment strategies used and is part of a larger study to evaluate the feasibility of the care model. Objective: To describe our experience executing three different strategies to recruit hypertensive patients in the program: community hypertension screenings, hospital and pharmacy referral. Methods: Individuals with elevated blood pressure and no history of cardiovascular disease were referred to the program's recruitment days to see a medical doctor for hypertension diagnosis and enrollment. Individuals were referred from community screenings, tertiary hospital outpatient clinics, and pharmacies participating in the program. For the community screenings, we report the number needed to screen (NNS) to find one individual with elevated blood pressure, the NNS to enroll one individual in the program, and factors associated with enrollment in the program among participants referred. Results: We recruited 226 individuals (69%) in the program via the pharmacies, 97 (30%) via the community screenings, and 2 (<1%) via hospital referral. At the community screenings 3,204 individuals participated, 729 (23%) had elevated blood pressure and 618 (85%) were eligible for referral of whom 142 (23%) visited the recruitment days, and 97 (16%) enrolled. The NNS to find one individual with elevated blood pressure was 5, and the NNS to enroll one individual was 34. Enrollment in the program was associated with advancing age, blood pressure ≥160/100 and currently using antihypertensive medication. Conclusions: Despite the potential attractiveness of community screenings to identify and refer individuals with hypertension, enrollment in the program was low. For future programs we recommend pharmacy referral as individuals seem more inclined to access care through healthcare providers they are familiar with.